Complete mitochondrial genome of the megamouth shark Megachasma pelagios (Chondrichthyes, Megachasmidae) - Chang, Chia-Hao; Shao, Kwang-Tsao; Lin, Yeong-Shin; Chiang, Wei-Chuan; Jang-Liaw, Nian-Hong (My University, 2014)
Here we describe the complete mitochondrial genome sequence of the megamouth shark, Megachasma pelagios, which is an extremely rare species of deepwater shark. The circle genome (16,694 bp) consists of 13 protein coding, 22 tRNA, 2 rRNA genes and 1 control region. It has the typical vertebrate mitochondrial gene arrangement.
Keywords: Complete mitochondrial genome; Megachasma pelagios; megamouth shark